Sustainable Future: Trends, Strategies and Development Proceedings of the 3rd Conference on Managing Digital Industry, Technology and Entrepreneurship, (CoMDITE 2022), Bandung, Indonesia, 24 May 2022 - Noviaristanti, Siska; Boon, Ong Hway (Taylor & Francis, 2023)
The book contains a selection of papers that were presented at the 3rd Conference in Managing Digital Industry, Technology and Entrepreneurship (3rd CoMDITE) with the theme: Sustainable Future: Trends, Strategies and Development. The Millennium Development Goals, continued as Sustainability Development Goals (SDGs), are effective instruments and have, in recent years, brought many positive changes in numerous countries around the world. Most notably, it has fundamentally changed our way of approaching the tangled set of challenges: States today undertake to achieve concrete development goals; transparency and accountability to citizens and the global public has become a matter of course; and cooperation between the political, economic and societal spheres is no longer questioned. However, in addition to the global pandemic situation it has challenged the business world to develop an outstanding strategy to face extreme uncertainty. Using digital technology and its advancement is believed to be one of the main keys for taking up this challenge. The 3rd Conference in Managing Digital Industry, Technology and Entrepreneurship (the 3rd CoMDITE) has brought forward discussions on implementation of digital technology in strategic, operation, finance, marketing, human resources management, and entrepreneurship around sustainable future issues. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. 　 Funded by Telkom University, Indonesia.